Tinjauan Hukum Islam terhadap Kawing Soro' Pada Masyarakat Bugis Kabupaten Bone - Syawaluddin Hanafi; Anita Marwing; Arini Pratiwi (Al-Mizan (e-Journal), 2019)
This study aims to determine the behavior of the Bugis community in Bone Regency in carrying out marriage. The development of marital culture and customs in the Bugis community in bone district, especially in terms of kawing soro’ became the main focus of this research. This research is a qualitative research with Islamic law approach. The results of this study found that habits in people's lives that were considered to be full of spiritual meaning became worthless after the existence of some Bugis communities in the district of Bone who performed kawing soro'. On the other hand, kawing soro' becomes compulsory if adultery is feared, in another sense that kawing soro' can be done if there are forced or emergency conditions. The Bugis community in Bone Regency who implements kawing soro' basically wants to carry out the commands of Allah and their Rasul, but it is not understood by the community that couples who do kawing soro', the husband is obliged to pay dowry even though only giving half and the wife may refuse to give the husband's rights like hanging out and having sex before the wife receives the specified dowry introduction.